Germanisms in idioms in the Slovar slovenskega knjižnega jezika (Standard Slovenian Dictionary) from R to Ž - Stramljič Breznik, Irena; Hameršak, Marjana (Jezikoslovni zapiski, 2015)
This article presents the final part of a study (R–Ž) of Germanisms in the Slovar slovenskega knjižnega jezika (Standard Slovenian Dictionary, SSKJ) that are also elements of idioms. Based on their dictionary labels, these idioms are analyzed in terms of correlation between marked Germanism and therefore also marked idiom; however, the contemporary use and knowledge of these idioms were assessed using the FidaPLUS reference corpus and a questionnaire completed by fifty-four second-year students in the single-discipline undergraduate program in Slovenian at the University of Maribor’s Faculty of Arts.